Dynamic Response Characteristics of Composite Concrete Structures Subjected to Reactive Jet Impact - Chenghai Su; Peiyu Li; Jiahao Zhang; Aoxin Liu; Yuanfeng Zheng; Haifu Wang (Buildings, 2024)
Composite concrete structures, commonly found in urban infrastructures, such as highways and runways, are pivotal research object in the protection field. To study the dynamic response of composite concrete structures subjected to reactive jet penetration coupled with an explosive effect, a full-scale damage experiment of composite structures under the action of 150 mm caliber shaped charges was performed, to derive the dynamic damage modes of different concrete thicknesses under the combined kinetic and chemical energy damage effects. The results indicated that under aluminum jet penetration, concrete layers exhibited minor funnel craters and penetration holes. However, concrete layers displayed a variety of damage modes, including central penetration holes, funnel craters, bulges, and radial/circumferential cracks when subjected to the PTFE/Al jet. The area of the funnel crater expanded as the thickness of the concrete increased, while the height of the bulge and the number of radial cracks decreased. The diameter of penetration holes increased by 76.9% and the area of funnel crater increased by 578% in comparison to Al jet penetration damage. A modified-RHT concrete model that reflected concrete tensile failure was established, utilizing AUTODYN. Segmented numerical simulations of damage behavior were performed using the FEM-SPH algorithm and a restart approach combined with reactive jet characteristics. The spatial distribution characteristic of the reactive jet and the relationship between kinetic penetration and explosion-enhanced damage were obtained by the simulation, which showed good concordance with the experimental results. This study provides important reference data and a theoretical basis for the design of composite concrete structures to resist penetration and explosion.